2021
DOI: 10.1021/acs.jpclett.1c03767
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling White Light Emission of a One-Dimensional Cu(I)-Based Organometallic Halide toward Single-Phase Light-Emitting Diode Applications

Abstract: Luminescent organometallic halide crystals, especially with single-component white emission, are urgently needed for light-emitting diode (LED) applications. Barriers for the applications, however, lie in their lead toxicity, poor stability, and low photoluminescence quantum yield (PLQY). Here, a one-dimensional Cu­(I)-based hybrid metal halide (C12H24O6)­CsCu2Br3 is designed and prepared via a simple solution method. Upon 365 nm excitation, a broad-band white light emission centered at 535 nm with a full widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The generation of white light has been an area of active research, due to its potential applications in organic electronics and biophysical chemistry. Its inherent mechanism is usually believed to involve a cascade energy transfer pathway in complex systems containing multiple emitting species; still, it is also possible that the observed white light is simply a sum of emissions in different spectral regions, from the components of the system. Of the various strategies for assembling multichromophoric systems for this purpose, surfactant-induced aggregation is convenient and reliable. In recent times, this modality has been exploited to obtain aggregation-induced enhancement of emission (AIEE). The study presented here explores the potential of one such aggregate in the design of novel white light-emitting platforms, in conjunction with protein amyloid fibrils. The implications of amyloid fibrils in neurological diseases prompted a frenzy of activity in the field of inhibition of aggregation and/or fibrillation. More recently, however, more attention has been paid to the prospect of amyloid fibrils as functional biomaterials, , with potential applications in drug delivery, analyte sensing, and bioengineering and as templates for self-assembly .…”
mentioning
confidence: 99%
“…The generation of white light has been an area of active research, due to its potential applications in organic electronics and biophysical chemistry. Its inherent mechanism is usually believed to involve a cascade energy transfer pathway in complex systems containing multiple emitting species; still, it is also possible that the observed white light is simply a sum of emissions in different spectral regions, from the components of the system. Of the various strategies for assembling multichromophoric systems for this purpose, surfactant-induced aggregation is convenient and reliable. In recent times, this modality has been exploited to obtain aggregation-induced enhancement of emission (AIEE). The study presented here explores the potential of one such aggregate in the design of novel white light-emitting platforms, in conjunction with protein amyloid fibrils. The implications of amyloid fibrils in neurological diseases prompted a frenzy of activity in the field of inhibition of aggregation and/or fibrillation. More recently, however, more attention has been paid to the prospect of amyloid fibrils as functional biomaterials, , with potential applications in drug delivery, analyte sensing, and bioengineering and as templates for self-assembly .…”
mentioning
confidence: 99%
“…In previous studies, the white light emission in hybrids mainly concentrated on optimizing polyhedral guests, involving the introduction of additional luminescent metals, 29,31,34,36 modulation of halogens, 37 defect-induced charge transfers 38 and other ways. 39 However, investigations on organic hosts still remain in their infancy. Recently, zerodimensional lead-free metal hybrids, such as In-based metal halides, involving (C 4 H 14 N 2 In 2 Br 10 ), 40 Cs 2 InBr 5 •H 2 O 11 and (PMA) 3 InBr 6 , have emerged as superior emitters.…”
Section: Introductionmentioning
confidence: 99%
“…29 First-principles calculations revealed that the broadband emission of CsCu 2 X 3 originates from the self-trapped excitons in semiconductors with localized charge carriers. 30–32 It is worth noting that Cu NPs can successfully improve the optical performance through LSPR. 33…”
Section: Introductionmentioning
confidence: 99%
“…28 Recently, a series of non-toxic and highly stable Cu halides CsCu 2 X 3 (X = Cl, Br, I) were synthesized. [29][30][31][32] A representative example is the non-toxic CsCu 2 X 3 (X = Cl, Br, I) family that exhibits highly efficient emission properties with PLQY values of up to 48%, as well as improved thermal and air stability. 29 First-principles calculations revealed that the broadband emission of CsCu 2 X 3 originates from the self-trapped excitons in semiconductors with localized charge carriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation